1977
DOI: 10.1111/j.1651-2227.1977.tb07928.x
|View full text |Cite
|
Sign up to set email alerts
|

ATOPIC DISEASE IN SEVEN‐YEAR‐OLD CHILDREN Incidence in Relation to Family History

Abstract: The incidence of atopic disease and its relation to the family history was studied by questionnaire in 1325 children, 7 years of age. A higher incidence of bronchial asthma (2.7%) was found than in a previous Swedish study. The total incidence of atopic disease in the children was 15.1% with a higher level when there was a double parental history of such disease (42.6%) as compared with a single such history (19.8%). When both parents had an identical type of atopic disease, i.e. respiratory or skin, the incid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
48
2
5

Year Published

2005
2005
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 209 publications
(59 citation statements)
references
References 14 publications
4
48
2
5
Order By: Relevance
“…Many physicians have investigated the genetic relationships between AD and psoriasis, and genomic imprinting in these two conditions shows different patterns [10]. These dermatoses are not hereditary disorders, but the incidence of children with AD from parents with atopic (allergic) disease are higher than that from parents or one parent without atopic (allergic) disease [11,12]. Stefanie [6] suggests that antigen-specific T-cell subsets determine the pathogenesis of psoriasis and atopic eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Many physicians have investigated the genetic relationships between AD and psoriasis, and genomic imprinting in these two conditions shows different patterns [10]. These dermatoses are not hereditary disorders, but the incidence of children with AD from parents with atopic (allergic) disease are higher than that from parents or one parent without atopic (allergic) disease [11,12]. Stefanie [6] suggests that antigen-specific T-cell subsets determine the pathogenesis of psoriasis and atopic eczema.…”
Section: Discussionmentioning
confidence: 99%
“…Çocukta AR gelişme riski; anne-babada alerji öyküsü yoksa %0-10, annebabadan birisinde alerji öyküsü varsa %30-40, anne ve babanın her ikisinde de alerji öykü-sü varsa %60-70 oranındadır. [32] Monozigotik ikizlerde yapılan çalışmalarda dizigotiklerden daha yüksek oranda AR görülmesi de genetik geçişi desteklemektedir. Yedi bin İsveç'li ikizde yapılan çalışmada monozigotik ikizlerde %45, dizigotiklerde ise %25 oranında; ayrıca 3.808 Avustralya'lı ikizde yapılan çalışmada monozigotiklerin %61'inde dizigotiklerin ise %25'inde aynı anda AR görülmüştür.…”
Section: Genetik Geçiş (Alerjik Hastalık Ve Atopi öYküsü)unclassified
“…[33,34] Mevsimsel AR'li hastaların %46'sında, perennial AR'lilerin ise %49'unda ailesel atopi öyküsü bulunduğu bilinmektedir. [32,35] …”
Section: Genetik Geçiş (Alerjik Hastalık Ve Atopi öYküsü)unclassified
“…If both parents are affected the figure increases up to 40-60%, and 50-80% if both show the same allergic manifestations. The risk of atopy in children who have an allergic sibling ranges between 25 and 35% [3,10].…”
Section: Introductionmentioning
confidence: 99%
“…If both parents are affected the figure increases up to 40-60%, and 50-80% if both show the same allergic manifestations. The risk of atopy in children who have an allergic sibling ranges between 25 and 35% [3,10].The importance of genetic factors is also demonstrated by other data:(I) children with positive family history for atopy develop allergic symptoms earlier than those with a negative family history [11], (II) The higher the incidence the higher the number of affected subjects in the same family [3].Notable differences exist in the so-called predisposition to atopic diseases, and further study appears to be necessary to better delineate the role played by genetic factors in the development of such disorders.In many allergic patients total serum IgE levels are found to be elevated, and it has been shown that a high total serum IgE level in infants is often associated with the subsequent development of atopic symptoms. Therefore, it was proposed that the measurement of IgE by PRIST testing in infants or at birth would have a predictive value in the atopy development.…”
mentioning
confidence: 99%